(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Palmer type IB triangular fibrocartilage complex is one of the most common cause of ulnar wrist pain. The main surgical treatment for this lessions are open and wrist arthroscopic technique to repair TFCC. Our study was carried out to describe the result of both techniques in the treatment of type IB TFCC injuries. Methods: The study was carried out by a retrospectively on 29 patients, all of whom are sugical treated at Hospital of Traumatology and Orthopedic of Ho Chi Minh city from 2019 to 2021. Results: there was 21 female patients with mean age 35,2±7,1 years old and 8 male patiens with mean age 19,1±1,8 years old. In which, 15 patients underwent arthroscopic surgery, according for 51,72% and 14 underwent open surgery, according for 48,28%. The mean follow-up time of arthroscopic group was 19,33±6,31 months, and in open surgery group was 18,93±4,13 months. The mean VAS score in arthroscopic group was 1,2±1,47 and in open surgery group was 0,57±0,62 at the time of final follow-up (p>0,05). The arthroscopic group had an average score of 83,33±12,06 and the open surgery group was 88,21±6,97 on the Mayo modified wrist score (p>0,05). In all cases, there were 12 excellent cases, 12 good cases, 4 satisfactory cases and 1 poor case. The comon complications in arthroscopic group were ulnar nerve injuries in 3 cases and prominent surture knot in 2 cases, followed by extensor carpi ulnaris tendonitis in 1 case. In open surgery group, there were 3 cases ofprominent surture knot and 1 case of pin infection. Conclusion: Both techniques of treating Palmer IB trianglar fibriocartilage complex injuries gave similar good results, the choice of method depends on the surgeon’s reference. However, the risk of ulnar nerve injury was higher in the arthroscopic group.